Health-related patterns and chronic kidney disease in the Brazilian population: National Health Survey, 2019 - Letícia Cristina Machado de Sousa; Nathalia Rabello Silva; Catarina Machado Azeredo; Ana Elisa Madalena Rinaldi; Luciana Saraiva da Silva (Frontiers Media S.A., 2023)
ObjectiveThe aim of this study was to identify patterns related to health and their association with chronic kidney disease (CKD) in the Brazilian population.MethodsWe used data from the National Health Survey (PNS), 2019. Participants were interviewed and answered questions related to socioeconomic and demographic information (gender, age, education, race/color), health conditions (presence of hypertension, diabetes mellitus, hyperlipidemia, cardiovascular disease, overweight and CKD) and lifestyle (smoking, alcohol consumption, physical activity and food consumption). To identify patterns, we used exploratory factor analysis. We performed logistic regression models to describe the association of CKD with each pattern in crude models and adjusted for gender, age group, education level and race/color.ResultsA total of 90,846 individuals were evaluated. The prevalence of CKD was 1.49% (95% CI: 1.3-1.6). Three health-related patterns - metabolic factors, behavioral risk factors and behavioral protective factors - were identified by factor analysis. Metabolic factors were determined by the presence of hypertension, diabetes mellitus, hyperlipidemia and cardiovascular diseases. Behavioral risk factors were determined by smoking, alcohol consumption, regular consumption of soft drinks, sweets and artificial juices, and high salt consumption. The protective behavioral factors were established by the practice of physical activity and regular consumption of vegetables and fruits. Participants of the highest tertile for metabolic factors were more likely to have CKD in the adjusted model (OR = 3.61, 95% CI: 2.69-4.85), when compared to those of the lower tertile.ConclusionThe pattern referring to metabolic factors was associated with a higher chance of presenting CKD.